3D printing of a palladium-alumina cermet monolithic catalyst: catalytic evaluation in microwave-assisted cross-coupling reactions. (January 2023) - Tubio, C.R.; Malatini, C.; Barrio, V.L.; Masaguer, C.F.; Amorín, M.; Nabgan, W.; Taboada, P.; Guitián, F.; Gil, A.; Coelho, A.
Abstract: A straightforward manufacture strategy is proposed to obtain an efficient and robust palladium-alumina (Pd 0 /Al2 O3 ) cermet monolithic catalyst, specifically designed to perform safe microwave assisted organic synthesis (MAOS). In this approach, a cermet catalyst with high surface area, controlled composition and adapted shape and dimensions to a microwave reactor vessel is generated via 3D printing technology and sintering. The resulting catalyst has been explored in heterogeneous Suzuki, Sonogashira, Stille and Heck cross-coupling reactions, in MAOS. The Pd 0 catalyst is permanently active, stable, without leaching and can be recycled and reused at least 200 reaction cycles. The generation of hot spots, sparking or hazardous discharges is controlled by the effective immobilization of the palladium in the monolithic structure during the reaction. The palladium content is forming part of both the internal and external structure, providing greater mechanical resistance and catalytic activity with respect to the basic ceramic material (alumina). Graphical abstract: Image 1 Highlights: 3D Printing of a Palladium-Alumina Cermet Monolithic Catalyst. Monolithic catalyst, specifically designed to perform safe microwave assisted organic synthesis. Pd 0 catalyst is active, stable, no leaching, can be recycled and reused 200 reaction cycles. CERMET fabricated through direct ink writing technique, followed by sintering. Inner/outer Pd content, providing mechanical resistance and catalytic activity.